2011
DOI: 10.1074/jbc.m110.197400
|View full text |Cite
|
Sign up to set email alerts
|

Deimination of Human Filaggrin-2 Promotes Its Proteolysis by Calpain 1

Abstract: Filaggrin-2 (FLG2), a member of the S100-fused type protein family, shares numerous features with filaggrin (FLG), a key protein implicated in the epidermal barrier functions. Both display a related structural organization, an identical pattern of expression and localization in human epidermis, and proteolytic processing of a large precursor. Here, we tested whether FLG2 was a substrate of calpain 1, a calcium-dependent protease directly involved in FLG catabolism. In addition, deimination being critical for F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
113
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(122 citation statements)
references
References 58 publications
6
113
2
1
Order By: Relevance
“…The effect of keratin deimination is not really known, but it is concomitant with and therefore could be involved in the modifications of the intracorneocyte fibrous matrix observed at the ultrastructural level. In addition, PAD1 and/or PAD3 could be involved in the deimination of filaggrin-2, a recently described protein of the S100-fused type protein family that may participate in the formation of the NMF (Hsu et al, 2011). The epidermal targets and the function of PAD2 in the epidermis have not been identified so far.…”
Section: Peptidylarginine Deiminases In the Epidermismentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of keratin deimination is not really known, but it is concomitant with and therefore could be involved in the modifications of the intracorneocyte fibrous matrix observed at the ultrastructural level. In addition, PAD1 and/or PAD3 could be involved in the deimination of filaggrin-2, a recently described protein of the S100-fused type protein family that may participate in the formation of the NMF (Hsu et al, 2011). The epidermal targets and the function of PAD2 in the epidermis have not been identified so far.…”
Section: Peptidylarginine Deiminases In the Epidermismentioning
confidence: 99%
“…It has been found that filaggrin, filaggrin-2, keratin 1 (K1) and keratin 10 (K10) in the epidermis (Senshu et al, 1996;Kamata et al, 2009;Hsu et al, 2011), as well as trichohyalin and S100A3 in the hair follicles are the major deiminated proteins (Rogers et al, 1997;Tarcsa et al, 1996Tarcsa et al, , 1997. The presence of deiminated proteins mainly in the stratum corneum suggests a function for deimination during cornification, the last steps of terminal differentiation of keratinocytes.…”
Section: Deimination and Peptidylarginine Deiminases In Skin Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Later studies involving genomic wide associations studies (GWAS) have reported associations with variants at the c11orf30 locus (polysensitization of allegen) [41], STAT6 gene (allergic sensitization and serum IgE) [42], and CAPN14 (calcium regulated protease that is highly expressed in esophageal mucosa and is associated with filaggrin) [43]. Future studies will lead to more information of the role of genetics in this complicated interplay of genes and environment.…”
Section: Geneticsmentioning
confidence: 99%